International census of Whooper Swans Cygnus cygnus in Britain, Ireland and Iceland: January 1991 - Kirby, Jeff S; Rees, Eileen C; Merne, Oscar J; Gardarsson, Arnthor (Wildfowl, 1992)
A coordinated census of Whooper Swans wintering in Britain, Ireland and Iceland was made in January 1991. A total of 18,035 birds was counted, and these are thought to represent most of the Icelandic-breeding population. Of the total number recorded, 5225 (29.0%) were counted in Britain, 3484 (19.3%) in Northern Ireland, 8490 (47.1%) in the Irish Republic and 831 (4.6%) in Iceland. The distribution of the flocks is described in further detail and the results compared with the census made in January 1986. There was considerable variation in the proportion of juveniles recorded in different parts of the wintering range. Possible reasons for this variation are discussed.